PERAN PETUGAS DALAM PENYALURAN BANTUAN SOSIAL DI DESA TAMAILA KECAMATAN TOLANGOHULA KABUPATEN GORONTALO - Nurlin Kaje (Universitas Bina Taruna Gorontalo, 2024)
This research aims to find out the role of village officials in distributing social assistance in Tamaila Village, Tolangohula District, Gorontalo Regency. This research uses a descriptive method with a qualitative approach. Data collection was carried out through observation, interviews and documentation related and relevant to this research. Social assistance provided by the government is a form of government concern for its people. This is in accordance with the constitutional mandate that the poor and neglected children are cared for by the state. The research results show that officers in distributing social assistance are not transparent, where it is not clear how much social assistance should be received by residents who are obliged to receive it. Officers did not properly collect data on who was eligible and obliged to receive social assistance, where there were residents who were not recorded even though they deserved to receive it. Officers show favoritism in distributing social assistance because the priority is relatives and those closest to them who always support the village head's directions. This element of intentionality is associated with anyone who does not vote in the village head election so that it is ignored and makes things difficult in various ways, especially getting social assistance. For this reason, it can be concluded that the distribution of social assistance carried out by officers is not yet transparent, there is favoritism and data collection on residents receiving social assistance is not accurate because something has been overlooked. For this reason, it is recommended that the distribution of social assistance must receive strict supervision.